Education on Sanitation and Hygiene Knowledge on Food Vendors in Semolowaru Culinary Tourism Center (CTC) Surabaya - Mauren Gita Miranti; Sri Handajani; Lucia Tri Pangesthi; Nugrahani Astuti; Asrul Bahar; Andika Kuncoro Widagdo (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
The aims of this community service viceeise are to 1) increase the awareness of traders regarding the application of hygiene sanitation and food safety and 2) improve the skills of traders in maintaining the sanitation of the kitchen environment so that a healthy culinary tourism center will be created. Education is provided with presentations, demonstrations, and questions and answers. This research is a descriptive observational study, with a sample of 24 food and beverage traders. The data collection technique used a written test and observation. The results showed that 1) the traders' initial knowledge about sanitation hygiene and food safety was very low, and the awareness of traders regarding the application of hygiene sanitation, and food safety as seen from the traders' understanding of hygiene sanitation and food safety had increased significantly based on the results of the pre and post-test, and 2) The personal hygiene attitude of food vendors is quite good, but there is one very lacking indicator, namely the cleanliness of the equipment. This implies that educational activities regarding hygiene sanitation for food business actors are needed to improve food quality through changes in knowledge and attitudes in a positive direction so that consumer health will be more secure.